Entre defesa e ordem: os corpos militares da Paraíba na trama da subordinação à capitania de Pernambuco (1755 1799) - Silva, Bruno Cezar Santos da (2014)
This master's research, linked to the Regional History and concentrated in History and Historical culture, intends to analyse the composition, operation and distribution of military bodies settled in the captaincy of Paraíba in the period from 1755 to 1799, at which time this was subordinated, military and administratively, to the captaincy of Pernambuco, giving a particular focus to the government of Jerônimo José de Melo e Castro (1764-1797) and to the military reforms made by Sebastião José de Carvalho e Melo, Count of Oeiras, future Marquess of Pombal and the present main secretary of the king José I (1755/6-1777). Moreover, we aim to peer the involvement of members of these bodies, notably those from the top of military corps, in the plots of power that engendered this colonial society and, at the same time, evaluate how the loss of political and administrative autonomy interfered in the maintenance of the troops and governing capability of captains mores of the captaincy of Paraíba. For this purpose, we adopted as a research referencial, as well as the concerning bibliography, with emphasis on the perspective of "New Political History" and the resulting notion of "Political Culture", the documentation of the Overseas Historical Archive.